Difficulties of Elementary School Students in Writing Poetry: Kesulitan Siswa Sekolah Dasar dalam Menulis Puisi - Ina Fitria; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the difficulties of elementary school students in writing poetry and to describe the factors of the difficulties of elementary school students in writing poetry. This study describes descriptively the difficulties of students in writing poetry. The method of data collection in the core research is carried out by means of a literature study method that has been studied and analyzed by the researchers themselves. The results obtained from this study are that students have difficulty determining the title/idea or theme in writing poetry, students have difficulty making rhythmic words, students have difficulty making imaginative sentences, students have difficulty making diction words or sentences. Meanwhile, the factors that make it difficult for students to write poetry are external factors, namely the teacher has not used innovative learning strategies, approaches, models and methods, and, the teacher has not used innovative learning media.